Potensi Pengembangan Investasi Berbasis Ekonomi Kreatif Di Kota Denpasar - Wiagustini, Ni Luh Putu; Meydianawthi, Luh Gede; Mustanda, I Ketut; Abundanti, Nyoman (Jurnal Ekonomi Kuantitatif Terapan; 2017: Vol. 10, No. 2, Agustus 2017 (pp. 110 - 252), 2017)
This research aimed to analyze Investment Potentials and Investment Business Climate based on Creative Economies in Denpasar City. To achieve this research objective, Location Quotient (LQ), Anova, and Performance-Importance Analysis techniques were employed. This study utilized both secondary and primary data. The results showed that creative economy-based investment potentials and those which were expandable in Denpasar City including: Handicraft, Printing and Publishing, Fashion, Culinary and Music. There were differences in the impact of Number of Workforce and Investment and Economic Value per Creative Economy Sub-Sector as follows: the workforce posed significant impact on Handicraft, Printing and Culinary; while Investment and Economic Value significantly impacted Handicraft, Fashion and Culinary. Developments of creative economy-based investments which need to be prioritized, given attention to and properly handled by Denpasar City Government including: (i) Operational efficiency assistance, (ii) Product marketing assistance, (iii) Assistance in human resources quality improvement, (iv) Assistance in funding fulfillment through loans, (v) Assistance in maintenance of activity sustainability, (vi) Government assistance in product distributions.